Current perspectives on the etiology and manifestation of the “silent” component of the Female Athlete Triad - Mallinson, Rebecca J (Dove Medical Press, 2014)
The Female Athlete Triad (Triad) represents a syndrome of three interrelated conditions that originate from chronically inadequate energy intake to compensate for energy expenditure; this environment results in insufficient stored energy to maintain physiological processes, a condition known as low energy availability. The physiological adaptations associated with low energy availability, in turn, contribute to menstrual cycle disturbances. The downstream effects of both low energy availability and suppressed estrogen concentrations synergistically impair bone health, leading to low bone mineral density, compromised bone structure and microarchitecture, and ultimately, a decrease in bone strength. Unlike the other components of the Triad, poor bone health often does not have overt symptoms, and therefore develops silently, unbeknownst to the athlete. Compromised bone health among female athletes increases the risk of fracture throughout the lifespan, highlighting the long-term health consequences of the Triad. The purpose of this review is to examine the current state of Triad research related to the third component of the Triad, ie, poor bone health, in an effort to summarize what we know, what we are learning, and what remains unknown.